ANALISIS PENGETAHUAN PERAWAT TERHADAP PENERAPAN DOKUMENTASI ASUHAN KEPERAWATAN BERBASIS SDKI, SIKI DAN SLKI - Wijaya, Leni; Juniarti, Fudjie (Jurnal Kesehatan dan Pembangunan, 2025)
The quality of nursing care documentation through the implementation of 3S standards (SDKI, SIKI, SLKI) is still largely not in accordance with the standards. One of the main factors that influences the implementation of 3S-based nursing documentation is nurses' knowledge. The purpose of this study was to determine the relationship between nurses' knowledge and the implementation of 3S-based nursing care documentation. This research method uses a correlational design with a cross-sectional approach. The sample in this study were 60 nurses in the Inpatient Room of Pusri Hospital, the sampling technique used was total sampling. The analysis of this study used the Chi-Square test. The results of this study were that there was a relationship between nurses' knowledge and the implementation of SDKI, SIKI and SLKI-based nursing care documentation with a p-value of 0.000 <? 0.05. Suggestions for nurses to be motivated to increase their knowledge of the implementation of 3S-based nursing care documentation standards by conducting book reviews or attending seminars on the implementation of 3S-based nursing care documentation as well as routine supervision and in-house training can be carried out by the nursing committee. So that nurses with good knowledge accompanied by the implementation of nursing care documentation according to SDKI, SIKI and SLKI standards can improve the quality of optimal health services